Extraction and Separation of Rare Earths from Nitrate Medium by Mixtures of p‐Phosphorylated Calixarene and 1‐Phenyl‐3‐methyl‐4‐benzoyl‐pyrazalone‐5. Issue 10 (29th September 2014) - Lu, Youcai; Li, Yanling; Bi, Yanfeng; Liao, Wuping
Abstract The gadolinium extraction by the mixtures of p‐phosphorylated calixarene and 1‐phenyl‐3‐methyl‐4‐benzoyl‐ pyrazalone‐5 from nitrate medium was studied, which indicated an obvious synergistic effect between these two extractants. The extractants exhibit no interaction with each other before the metal extraction. Gadolinium(III) was extracted by the species of Ln(PMBP)2L2(NO3) instead of Ln(PMBP)3·(HPMBP) or Ln(NO3)3·2L which are extracted by HPMBP or L alone. Thermodynamic functions (ΔG, ΔH, ΔS) were calculated. The extraction of other rare earths was also investigated and compared. Possible single rare earth separation was discussed.